Marginality as A Site of Youth Kurdish Resistance - Kaya, Ilhan (IOS PRESS, 2016)
Turkey was founded in 1923 as a classical nation state ignoring ethnic and cultural differences. It fallowed an assimilationist policy to melt all differences so that the nation was united and intact. It denied cultural and political rights of ethnic groups such as the Kurds. The denial of such rights resulted in the alienation and marginalization of the Kurds. However, the Kurds did not remain silent and developed diverse forms of resistance including a violent arm struggle. This paper argues that without a careful understanding the margin and experiences of those who have been pushed to the aside, it is not possible to end an ethnic conflict and reach a long lasting peace. Informed by Bell Hooks' theory of marginality, the paper tries to get a sense of the Kurdish youth's views and experiences of a violent and painful ethnic conflict going for almost a half-century. It also tries to understand the forms of resistance the Kurdish youth has developed to cope with oppression and domination.
Keywords: Marginality; Domination; the Kurdish conflict and Turkish nation state; International Relations; Government & Law